LENKĖ in the corpus of the contemporary Lithuanian language - Čižik-Prokaševa, Veslava (Lietuvių kalba, 2020)
The article examines the concept of a Polish woman in the Lithuanian language on the basis of nouns lenkė (Polish woman) and lenkaitė (young Polish woman). Based on the text from the Corpus of the contemporary Lithuanian language, it’s analyzed how the word lenkė is verbalized in the minds of Lithuanian language users, what kind of picture of a Polish woman consists of the selected material, what features characterizes her, how she differs from women of other nationalities.The article is based on an analysis of 158 sentences: 154 sentences are from the Corpus of the contemporary Lithuanian language and 4 sentences are from the Dictionary of the Lithuanian language. The majority of sentences shows, that people of Lithuania appreciate Polish women very well – 92 sentences; 40 sentences shows negative opinion, in 15 sentences are narrated about wrong, that Polish women suffer, and in 11 sentences Lithuanian and Polish women are appreciated as equivalent.In the Corpus of the contemporary Lithuanian language the basic features of a Polish woman are revealed in several crucial semantic aspects: mental, psychosocial, social, physical and domestic. The research showed that lenkė is a Polish nation woman, who is beautiful, educated, sporty, generous, deeply religious, talented, merciful, authoritative, and sometimes - when it’s talking about an older Polish woman - timid, angry, ugly and slovenly.